Service Improvement Program for P O HARUM BSI (The Indonesian Journal of Business Administration, 2015)
Abstract.PO Harum BSI is an autobus company that serves Indonesian inter-city and inter-province transportation. Currently, PO Harum BSI has an obstacle to run transportation services with Bandung-Palembang travel route, which is low perceived quality of bus transportation service. Target of service quality set by PO Harum BSI, which is bus transportation services that are above the service quality of the competitor.To achieve the company’s service quality target, PO Harum BSI should make strategy alternatives in order to increase its quality of service delivery and also leverage customers loyalty. The preparation of the strategy requires several approaches, include the external environment and internal environment scanning. After scanning the external and internal environment, SWOT Analysis can be generated as the summary of external and internal environment analysis.TOWS matrix provides strategy alternatives for PO Harum BSI. Based on the analysis, the proposed strategies are WO (Weaknesses-Opportunities) and WT (Weaknesses-Threats) strategies. The WO and WT Strategies will be conduct based on product, physical evidence, process, people, and place. The implementation plan of WO and WT Strategies will be made based on period and budget of each strategy. This implementation plan is expected can leverage the company's competitive advantages in bus transportation industry. Hence, PO Harum BSI can expand its business in order to maintain its existence.Keywords : Autobus company, Service quality, GAP analysis, TOWS matrix